PROSPECTS OF THE USE OF BUCCAL FAT PAD FOR CLOSING DEFECTS OF THE ALVEOLAR PROCESS OF THE JAWS - O. V. Ruzhytska (Український стоматологічний альманах)
In modern surgical dental practice, doctors often face the necessity to close the soft tissue defects of the oral cavity. In recent years numerous studies are aimed at developing such surgical techniques, which and promote the would provide sanation of the inflammatory focus, support physiological processes on sites of soft tissue defects or promote their recovery and normal functioning. The easy access to buccal fat pad continues to attract interest regarding its application for the closure of defects. The aim of work is to analyze and study the literature data on various techniques of application of buccal fat pad in autotransplantation for closing defects of the maxillofacial area in comparison with the use of other transplants. Results. In recent years, the reconstructive plastic surgery techniques in using autotransplantats have been paid much attention. In the literature there are data on the positive results of surgical closure of tissue defects by autotransplantation of adipose tissue and, in particular, the buccal fat pad. The buccal fat pad has its own connective tissue capsule and well-developed vascular net, provides nutrition to the transplant and rapid healing of the postoperative wound; does not require prior preparation and adaptation to the recipient's bed. It allows to use it in maxillofacial surgery to close the defects of the upper jaw, elimination of oral-antral connection, in the reconstruction of intraoral defects such as oral-antral fistula, with loss of bone mass of the lower jaw in the area of molars and premolars, to eliminate defects in cancer pathology of the face. Conclusions. Advantageous anatomical position, a good blood circulation and lack of innervation of buccal fat pad facilitates the task of surgeon and gives better results of operations. The study has shown the process of wound epithelialization occurs within a week after surgery as well as a stable clinical course without complications in the long-term follow-up that proves the relevance of the use of buccal fat pad in modern maxillofacial surgery in order to improve conventional methods of autotransplantation and to develop new ones.